The right to information for epilepsy patients in Brazil - Francisca Valéria Bezerra Sampaio Marques; Márcia Renata Mortari; Aline Alburquerque (Heliyon)
Epilepsy is one of the most common neurological conditions, affecting around 50 million people worldwide. It is characterized by a lifelong predisposition to recurrent epileptic seizures. In addition to the neurological and cognitive impacts, patients face social challenges such as discrimination, isolation and difficulties in accessing information. These factors affect their social inclusion and quality of life. In light of this, this article analyzes the importance of public policies that guarantee the right to information for people with epilepsy in Brazil. To this end, a bibliographical review of academic articles and legal documents related to the topic was carried out. The research sought to identify gaps in Brazilian legislation and highlight the need for new policies to ensure access to information. The results show that the lack of specific laws compromises this right, making it difficult to access adequate resources and support. This reinforces the need for new legislation and programs to ensure greater dignity and inclusion for these patients.